2008
DOI: 10.9775/kvfd.2008.03-a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Administration of Testosterone Antibody, β-Carotene and Vitamin E on Multiple Pregnancy and MDA (Malondialdehyde) in Tuj Breed Sheep in Non-Breeding Season

Abstract: Bu çalýşmada üreme mevsimi dýşýnda bulunan Tuj ýrký koyunlarda Testosteron antikoru, β-karoten ve E vitamini uygulamalarý ile çoğul gebeliğin artýrýlmasý ve MDA (Malondialdehit) düzeylerinin azaltýlmasý amaçlanmýştýr. Testosteron antikoru kastre edilmiş Tuj ýrký bir koçtan elde edildi. Çalýşma 29 adet koyunda 3 grup halinde yapýldý. Grup I'deki koyunlara (n=10) vaginal süngerlerin uygulanmasýndan 1 hafta önce testosteron antikoru, β-karoten ve E vitamini uygulandý. Grup II'deki (n=9) koyunlara testosteron anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…This results are higher than those reported for TW and LR on Akkaraman sheep 8 , and for FEC, LITS and LR 9 on Karakaş sheep and for LR 10,11 on Ramlıç and Tushin sheep.…”
Section: Reproductive Performance Of Ewes and Lamb Survival Rate (Sr)contrasting
confidence: 69%
“…This results are higher than those reported for TW and LR on Akkaraman sheep 8 , and for FEC, LITS and LR 9 on Karakaş sheep and for LR 10,11 on Ramlıç and Tushin sheep.…”
Section: Reproductive Performance Of Ewes and Lamb Survival Rate (Sr)contrasting
confidence: 69%
“…PMSG injection caused a 70% gestation rate. Kaçar et al (2008) reported a 50% gestation rate in Tuj sheep due to vaginal sponge application (containing 40 mg cronolone) and 600 I.U. PMSG injections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that β-carotene deficiency in feed adversely affects, either directly or indirectly, reproductive parameters such as estrus, conception, and pregnancy by changing ovary functions and intrauterine environment (Arıkan & Muğlalı 1999;Kaçar et al 2008). Özpınar et al (1994) reported that…”
Section: Discussionmentioning
confidence: 99%